Investigating surface treatments and coatings, their history, application and detection on selected pigments: Umber, Vine Black, Ultramarine Blue, Cu-Phthalocyanine Blue, and two Hansa Yellows, PY3 and PY74 - Ferreira, Cátia Beatriz da Costa (2018)
Pigment manufacture in the twentieth and twenty-first centuries has largely been intended for industrial application. Consequently, the artist’s materials market which is by contrast very small and specialized, relies on pigments produced for the industrial market. Improvements to enhance performance in an industrial context, has led to the introduction of a variety of different surface treatments applied to pigment particles. Pigment coatings can consist of one or more thin layers of either organic or inorganic material, or a combination of both. Their nature and their presence in very small amounts present a challenge for the detection and identification of these compounds. Part I of this thesis explores the literature covering pigment coating materials, application methods and the terminology used to identify the range and types of materials in use. Part II explores the analytical strategies that can be employed to detect these treatments on pigment samples. The pigments selected for this research include: Umber and Vine Black purchased from Kremer Pigmente during the Carlyle MOLART Fellowship for the creation of “historically accurate” paint reconstructions; Ultramarine Blue pigments since the use of coatings on these pigments is reported in the literature (for greater acid resistance); Cu-Phthalocyanine Blue pigments as these are currently amongst the most popular blue pigments; and the Hansa yellows, PY3 and PY74 from the manufacturer Royal Talens to determine the possible presence of a surface treatment or coating which could be responsible for paint instability. Analytical methods employed for this thesis work to characterize the organic fraction on pigments surfaces included: Evolved Gas Analysis Mass spectrometry (EGA/MS); Pyrolysis Gas Chromatography Mass Spectrometry (Py-GC/MS); Py-GC/MS using thermally assisted hydrolysis and methylation (THM) with gas chromatography-mass spectrometry (GC/MS) in combination with ultrafast thermal desorption (UTD), meaning the samples were investigated through “slow pyrolysis” and not as flash pyrolysis. This method, developed at RCE, involves a temperature program that enables a one-shot analysis with evaporation before pyrolysis. To characterize inorganic materials, the following instruments were used: Scanning Electron Microscope Energy Dispersive X-ray (SEM-EDX); (Scanning) Transmission Electron Microscope Energy Dispersive X-ray ((S) TEM-EDX); and Field Emission Gun Scanning Electron Microscope (FEG-SEM). Surface treatments influence the physical properties of pigments during the manufacture of coatings, including oil paints. By understanding their applications and chemistry and determining methods for identifying them in situ on pigment particles, their influence on the long-term stability within modern artist’s oil paint can be assessed.